2015
DOI: 10.1117/1.jrs.9.095989
|View full text |Cite
|
Sign up to set email alerts
|

Bio-optical model to describe remote sensing signals from a stratified ocean

Abstract: Abstract. We use a bio-optical model of the optical properties of natural seawater to investigate the effects of subsurface chlorophyll layers on passive and active remote sensors. A thin layer of enhanced chlorophyll concentration reduces the remote sensing reflectance in the blue, while having little effect in the green. As a result, the chlorophyll concentration inferred from ocean color instruments will fall between the background concentration and the concentration in the layer, depending on the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Analysis of SABOR data indicated that surface-weighted ocean-color-like properties yielded estimates of water column-integrated net primary production that consistently underestimated values calculated with vertically resolved data, with errors of up to 54% (Schulien et al 2017). The vertical plankton structure during SABOR was modest at best, and previous estimates of net primary production errors associated with a wider range in vertical structure indicate that such errors can exceed 100% (Platt & Sathyendranath 1988, Hill & Zimmerman 2010, Churnside 2015. These findings demonstrate the importance of plankton vertical structure for accurate assessments of ocean plankton stocks, productivity, and carbon cycling.…”
Section: Figurementioning
confidence: 55%
See 2 more Smart Citations
“…Analysis of SABOR data indicated that surface-weighted ocean-color-like properties yielded estimates of water column-integrated net primary production that consistently underestimated values calculated with vertically resolved data, with errors of up to 54% (Schulien et al 2017). The vertical plankton structure during SABOR was modest at best, and previous estimates of net primary production errors associated with a wider range in vertical structure indicate that such errors can exceed 100% (Platt & Sathyendranath 1988, Hill & Zimmerman 2010, Churnside 2015. These findings demonstrate the importance of plankton vertical structure for accurate assessments of ocean plankton stocks, productivity, and carbon cycling.…”
Section: Figurementioning
confidence: 55%
“…The result is that more than 92% of the ocean color signal emanates from the first optical depth (10-m geometric depth if the diffuse attenuation coefficient = 0.1 m −1 ), and 71% comes from the first half of the first optical depth (5 m for the same case). This limitation of ocean color can result in significant errors in important water column-integrated ocean properties, such as chlorophyll concentration (Sathyendranath & Platt 1989, Stramska & Stramski 2005 or net primary production (Platt & Sathyendranath 1988, Churnside 2015, Jacox et al 2015.…”
Section: Passive Ocean Color: Advances and Challengesmentioning
confidence: 99%
See 1 more Smart Citation